Flux Tube Entropy and Specific Entropy in Saturn's Magnetosphere. Issue 3 (11th March 2019) - Ma, Xuanye; Delamere, Peter A.; Thomsen, Michelle F.; Otto, Antonius; Neupane, Bishwa; Burkholder, Brandon; Nykyri, Katariina
Abstract: The motivation of this paper is to discuss the dynamical processes in Saturn's magnetosphere from the plasma entropy perspective. Saturn's magnetosphere is stabilized by a radially increasing profile of flux tube entropy and destabilized by a radially decreasing profile of flux tube content. The traditional radial transport scenario suggested that the magnetic flux with heavy flux tube content moves from the inner magnetosphere to the outer magnetosphere, stretching the magnetic field into a magnetodisc configuration. Subsequently, magnetic flux with low flux tube entropy generated by magnetodisc reconnection circulates back to the inner magnetosphere. However, the low‐specific entropy plasma with a narrow distribution in Saturn's inner magnetosphere suggests a significant nonadiabatic cooling process during the inward motion. The flux tube entropy analysis suggests that energetic particles dominate the total flux tube entropy in the magnetodisc region, and newly closed field lines generated by magnetodisc reconnection are likely to be transported into the inner magnetosphere. Based on the flux tube entropy constraint, this study demonstrates that the radial transport process in Saturn's magnetosphere can also be achieved via middle‐latitude double reconnection, driven by a low‐latitude interchange instability. This process does not involve significant latitudinal convection of magnetic flux in the ionosphere nor does it significantly modify the radial flux tube entropy profile. Key Points: Outward radial transport requires strong nonadiabatic heating source, while inward transport requires nonadiabatic cooling sink The hot component pressure strongly determines the penetration location of the reconnected flux tube Outward plasma transport could occur without significant modification of magnetic flux and flux tube entropy